2021
DOI: 10.3389/fimmu.2021.659339
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Mechanisms Underlying Gender Differences in COVID-19 Severity and Mortality

Abstract: Globally, over two million people have perished due to the recent pandemic caused by SARS-CoV-2. The available epidemiological global data for SARS-CoV-2 portrays a higher rate of severity and mortality in males. Analyzing gender differences in the host mechanisms involved in SARS-CoV-2 infection and progression may offer insight into the more detrimental disease prognosis and clinical outcome in males. Therefore, we outline sexual dimorphisms which exist in particular host factors and elaborate on how they ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 159 publications
(215 reference statements)
5
41
2
Order By: Relevance
“…Recent evidence points to the possible contributions of triggering and persistence of autoimmune activation in SARS-CoV-2-infected COVID-19 patients [ 2 , 3 ]. Intriguingly, despite classic autoimmune diseases being more prevalent in females, emerging studies have revealed a paradoxical male predominance of autoimmune activation in the setting of severe COVID-19 illness [ 4 ]. The extent to which such paradoxical sex differences in triggered autoimmunity may exist and persist across the broader clinical spectrum of SARS-CoV-2 infection is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence points to the possible contributions of triggering and persistence of autoimmune activation in SARS-CoV-2-infected COVID-19 patients [ 2 , 3 ]. Intriguingly, despite classic autoimmune diseases being more prevalent in females, emerging studies have revealed a paradoxical male predominance of autoimmune activation in the setting of severe COVID-19 illness [ 4 ]. The extent to which such paradoxical sex differences in triggered autoimmunity may exist and persist across the broader clinical spectrum of SARS-CoV-2 infection is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A third branch of research invests risk factors for specific groups: pregnant women [12], the elderly population [13,14], or specific regions [15][16][17], to name a few examples. While in the beginning, identifying risk factors was of primary interest, there are now also some attempts to understand possible mechanisms [18][19][20]. Unsurprisingly, the vast amount of research has led to an equally high number of systematic reviews and meta-analyses on risk factors [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This exposes them to considerably greater risks of critical COVID-19 outcomes [34][35][36][37]. Alongside this, various studies provide complementary explanations based on sexual dimorphisms [38]. Some in vivo experiments have shown the possible role of sex hormones in regulating ACE2 activity, essential for SARS-CoV-2 to enter the host cells in upper and lower respiratory tracts [39].…”
Section: Main Findingsmentioning
confidence: 99%